CESM1 CAM5 Decadal Prediction Large Ensemble ... - Yeager, S.; Danabasoglu, G.; Rosenbloom, N.; Strand, W.; Bates, S.; Meehl, G.; Karspeck, A.; Lindsay, K.; Long, M.; Teng, H.; Lovenduski, N. (UCAR/NCAR - Research Data Archive, 2025)
The CESM Decadal Prediction Large Ensemble (DPLE) is a set of simulations carried out at NCAR to support research into near-term Earth System prediction. The DPLE comprises 62 distinct ensembles, one for each of 62 initialization times (November 1 of 1954, 1955, ..., 2014, 2015). For each start date, a 40-member ensemble was generated by randomly perturbing the atmospheric initial condition at the round-off level. The simulations were integrated forward for 122 months after initialization. Observation-based ocean and sea ice initial conditions for the 1954-2015 period were obtained from a reanalysis-forced simulation of the CESM ocean and sea ice models. The initial conditions for the atmosphere and land models were obtained from CESM Large Ensemble (LENS) simulations at corresponding historical times. Full field initialization was used for all component models, and so drift adjustment prior to analysis is generally recommended. ...